2019
DOI: 10.1111/ejn.14540
|View full text |Cite
|
Sign up to set email alerts
|

The Bayesian‐Laplacian brain

Abstract: We outline what we believe could be an improvement in future discussions of the brain acting as a Bayesian‐Laplacian system. We do so by distinguishing between two broad classes of priors on which the brain's inferential systems operate: in one category are biological priors (β priors) and in the other artefactual ones (α priors). We argue that β priors, of which colour categories and faces are good examples, are inherited or acquired very rapidly after birth, are highly or relatively resistant to change throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 129 publications
(145 reference statements)
3
31
0
Order By: Relevance
“…An interesting corollary to the supposition that there are inherited brain concepts through which aesthetic judgments are interfaced is the extent to which individuals can update such concepts, or beliefs, in light of new experience, as is generally assumed in Bayesian inferential models. Some of our previous results showed that experiences such as color, interfaced through biologically inherited concepts, are more resistant to updating than those interfaced through acquired concepts (Zeki, 2011;Zeki & Chén, 2020). We emphasize that, even in the updating of beliefs based on biological concepts in light of experience, there are gradations; color categorizations represent perhaps an extreme in not allowing any significant updating, as do stimuli that have certain "significant configurations" that mark them as constituting a human face (Zeki, 2013;Zeki, Javier, & Mylonas, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An interesting corollary to the supposition that there are inherited brain concepts through which aesthetic judgments are interfaced is the extent to which individuals can update such concepts, or beliefs, in light of new experience, as is generally assumed in Bayesian inferential models. Some of our previous results showed that experiences such as color, interfaced through biologically inherited concepts, are more resistant to updating than those interfaced through acquired concepts (Zeki, 2011;Zeki & Chén, 2020). We emphasize that, even in the updating of beliefs based on biological concepts in light of experience, there are gradations; color categorizations represent perhaps an extreme in not allowing any significant updating, as do stimuli that have certain "significant configurations" that mark them as constituting a human face (Zeki, 2013;Zeki, Javier, & Mylonas, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Kant (1790Kant ( /1987 supposed that aesthetic experiences, as opposed to "utilitarian" experiences, are interfaced through "indeterminate" concepts and, as a consequence, the experiencing individual could assume that his or her aesthetic judgment has universal assent. We, on the other hand, suppose that there should be some considerable agreement between individuals belonging to different ethnic and cultural groups in the aesthetic judgment of faces because they are interfaced through inherited brain concepts that are shared among all humans (Zeki, 2011;Zeki & Chén, 2020), which appears to be the case (see also Langlois et al,1991;2000). In line with our supposition, other studies indicate that assent on the perceived attractiveness of faces between individuals is substantially higher than assent for stimuli that fall under the artifactual category (Vessel et al, 2018;Zeki & Chén, 2020); in other words, an individual's aesthetic judgment of faces corresponds better to his or her imagined aesthetic judgment that other individuals might make of the same face compared to the judgments that other indviduals' might make of abstract artworks (Leder, Goller, Rigotti, & Forster, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our next task is to determine how the brain handles aesthetic experiences derived from artifactual, man-made sources; we do not expect such experiences to be interfaced with inherited brain concepts, as in the experience of biological beauty. Rather, we expect that the experience of artifactual beauty is determined to a substantial degree by postnatally acquired concepts that are regularly updated in light of new experiences (Zeki 2009; Zeki & Chen, 2020). Whether such acquired concepts are also reflected in particular patterns in the relevant brain areas represents an important challenge for future studies in neuroesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…This gives at least a partial answer to what neural mechanisms underlie the “subjective” side of the equation, leaving open the other side, namely of what objective characteristics of the apprehended objects lead to activity in the sensory areas of the brain and which result in the engagement of the mOFC as well; for only when a sensory stimulus is experienced as beautiful is the mOFC engaged along with the sensory areas. To address this question experimentally, we restricted ourselves to studying one category of beautiful stimuli, namely that falling into the biological category (Zeki & Chen, 2020) and, within that category, confined ourselves further to studying the neurobiology underlying the experience of facial beauty.…”
Section: Introductionmentioning
confidence: 99%